Anti-SARS-CoV-2 and Immunomodulatory Activity of Marine Bacteria Polysaccharides - T. P. Smolina; N. V. Krylova; T. A. Kuznetsova; L. A. Ivanushko; A. K. Gazha; E. V. Persiyanova; O. S. Maistrovskaya; A. V. Gapeka; I. A. Belov; M. S. Kokoulin; M. Yu. Shchelkanov (Антибиотики и Химиотерапия, 2025)
Background. Intensive research is currently underway to ﬁnd new drugs to treat COVID-19, including the search for alternative antiviral treatments. Marine bacteria polysaccharides (PSs) are safe, biodegradable, and biocompatible polymers with a wide range of biological activity, including the ability to exert antiviral and immunomodulatory eﬀects. In this regard, PSs attract the close attention of scientists as a promising source of antiviral medicinal substances.The aim of the work is to evaluate the eﬀect of PSs from 3 diﬀerent species of marine bacteria on the expression of surface activation markers of innate immunity cells and to study their antiviral activity against the SARS-CoV-2 virus.Methods. The eﬀect of PSs on the expression of surface activation markers of innate immunity cells was studied by ﬂow cytoﬂuorometry. The study of the anti-SARS-CoV-2 activity of the PSs at the early stages of the virus life cycle was evaluated by inhibiting the cytopathogenic eﬀect of the virus (in the MTT assay) and by real-time reverse transcription polymerase chain reaction (RT-PCR-RV).Results. It was found that the studied PSs, diﬀering in chemical structure, induced activation of innate immunity cells (monocytes, neutrophils, NK cells) in vitro. The results obtained both in the test of inhibition of the cytopathogenic eﬀect of the virus and in reducing the level of RNA of the SARS-CoV-2 virus demonstrated the anti-SARS-CoV-2 activity of the PSs. PS1 showed the greatest activity, eﬀectively inhibiting the early stages of SARS-CoV-2 interaction with the cell. Conclusion. The studied PSs can be considered a promising source of antiviral medicinal substances.